Changes in cardiac autonomic modulation in women with breast cancer using aromatase inhibitors and the relation with biochemical variables - Gonzaga, Luana Almeida [UNESP] (2019)
Background: The use of autonomic modulation as a predictor of cardiovascular risk in women with breast cancer is important. Objective: To evaluate the cardiac autonomic modulation of postmenopausal women using aromatase inhibitors for breast cancer treatment, as well as its relation with the following biochemical variables. Methods: Postmenopausal women who did not have breast cancer (n = 33) and postmenopausal women with breast cancer (n = 15). For evaluation of the autonomic modulation the heart rate was recorded beat-to-beat for 30 minutes and the series of RR intervals obtained were used to calculate the following heart rate variability indices: Mean RR ms, SDNN (standard deviation of all normal RR intervals, expressed in milliseconds) ms, Mean HR, RMSSD (square root of the mean of the squared differences between adjacent normal RR interval) ms, NN50 (number of pairs of successive NNs that differ by more than 50 ms) count, pNN50% (proportion of NN50 divided by total number of NNs), RRtri (RR triangular), TINN (triangular interpolation of NN interval) ms, SD1 ms, SD2 ms, LF ms2, HF ms2, LH/HF ms2. The values of biochemical variables (fasting glycemia, triglycerides, HDL-cholesterol, and C-reactive protein) were analyzed by blood sample. Results: Lower values of heart rate variability indices were observed in postmenopausal women with breast cancer in relation to postmenopausal women who did not have breast cancer: Mean RR (p = 0.03); SDNN (p = 0.03); RMSSD (p = 0.03); NN50 count (p = 0.03); pNN50 % (p = 0.03); RRtri (p = 0.02); SD1 (p = 0.01); SD2 (p = 0.02); LF ms2 (p = 0.01); HF ms2 (p = 0.03).There was an inversely proportional correlation between the indices SDNN, SD2, and HFms2 with triglycerides (SDNN p = 0.04; SD2 p = 0.04; HF ms2 p = 0.04). No statistically significant correlations were found between heart rate variability indices and others variables. Statistical significance was set at 5% for all analyses. Conclusion: Women with breast cancer present reduced autonomic modulation and in these women of heart rate variability indices are inversely correlated with triglyceride values.